Utilization Of Peer Tutorial Methods In Improving Learning Outcomes Lay Up Shoot VIII Grade Students Of SMP N 4 Rejang Lebong - Muslan (Indonesian Journal of Sport, Health and Physical Education Science, 2023)
Physical education not only focuses on psychomotor aspects (skills), but also includes cognitive (knowledge) and affective (attitude). Learning models are often considered less varied and monotonous. This research method is class action research. The process of research in the classroom includes planning, action, observation, and reflection stages. Data collection techniques are performed by observing field (observation), interviews and documentation. The tools used are curriculum, RPP and assessment tools that cover emotional, cognitive and psychological aspects. The data analysis used is qualitative descriptive. The classical mastery that must be achieved on Lay Up Shoot learning is 75%. The grade of classical learning of period I was 73.77% (discontinuous). While the grade of classical learning finance of cycle II reaches 83.40% (finished). Improved student learning results after an even semester (graduated) by 0.8 with high criteria. The conclusion of this study is that there is an increase in learning to shoot weapons with peer tutors in class VIII students of Junior State 4 Rejang Lebong Year 2022. Researcher suggestion is that the use of peer instruction can be motivated for teachers to be more creative in developing learning processes, improving learning outcomes and Lay Up Shoot skills.